Combined gene deletion of dihydrofolate reductase-thymidylate synthase and pteridine reductase in Leishmania infantum - Bhattacharya, Arijit; Leprohon, Philippe; Ouellette, Marc (PLOS Neglected Tropical Diseases, 2021)
Our understanding of folate metabolism in Leishmania has greatly benefited from studies of resistance to the inhibitor methotrexate (MTX). Folates are reduced in Leishmania by the bifunctional dihydrofolate reductase thymidylate synthase (DHFR-TS) and by pteridine reductase (PTR1). To further our understanding of folate metabolism in Leishmania, a Cos-seq genome-wide gain of function screen was performed against MTX and against the two thymidylate synthase (TS) inhibitors 5-fluorouracil and pemetrexed. The screen revealed DHFR-TS and PTR1 but also the nucleoside transporter NT1 and one hypothetical gene derived from chromosome 31. For MTX, the concentration of folate in the culture medium affected the enrichment pattern for genes retrieved by Cos-seq. We generated a L. infantum DHFR-TS null mutant that was thymidine auxotroph, a phenotype that could be rescued by the addition of thymidine or by transfection of the flavin dependent bacterial TS gene ThyX. In these DHFR-TS null mutants it was impossible to obtain a chromosomal null mutant of PTR1 except if DHFR-TS or PTR1 were provided episomally. The transfection of ThyX however did not allow the elimination of PTR1 in a DHFR-TS null mutant. Leishmania can survive without copies of either DHFR-TS or PTR1 but not without both. Provided that our results observed with the insect stage parasites are also replicated with intracellular parasites, it would suggest that antifolate therapy in Leishmania would only work if both DHFR-TS and PTR1 would be targeted simultaneously.